2008
DOI: 10.1093/glycob/cwn144
|View full text |Cite
|
Sign up to set email alerts
|

Localization of O-glycans in MUC1 glycoproteins using electron-capture dissociation fragmentation mass spectrometry

Abstract: MUC1 is a mucin glycoprotein containing multiple tandem repeats of 20 amino acids, with five serines and threonines that can be O-glycosylated. Here, we investigated the O-glycosylation site occupancy in MUC1 glycoproteins produced in two mutant CHO cell lines, Lec3.2.8.1 and ldlD. We found that the average site occupancy was higher in MUC1 from Lec3.2.8.1 than from ldlD and that the occupancy increased with the number of tandem repeats in the protein and also depended on the culture conditions used for produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 22 publications
1
39
0
Order By: Relevance
“…studies found that mutagenesis of Thr 194 precluded apoE glycosylation (36), we propose that Thr 194 provides an initial and necessary site for apoE glycosylation and that this is followed by glycosylation of other sites on the C terminus. Such a stepwise pathway has been described for MUC1 (49).…”
Section: Determination Of Location Of Second Site Of O-glycosylation Inmentioning
confidence: 98%
“…studies found that mutagenesis of Thr 194 precluded apoE glycosylation (36), we propose that Thr 194 provides an initial and necessary site for apoE glycosylation and that this is followed by glycosylation of other sites on the C terminus. Such a stepwise pathway has been described for MUC1 (49).…”
Section: Determination Of Location Of Second Site Of O-glycosylation Inmentioning
confidence: 98%
“…Additionally, the exact glycosylation site of identified peptides containing several Ser/Thr residues cannot be predicted due to the lack of a consensus sequence for mucin-type O-glycosylation. The alternative fragmentation techniques electron capture dissociation (ECD) (38,39) and electron transfer dissociation (ETD) (40) have been introduced for site-specific analysis of CID-labile PTMs but characterization of protein O-glycosylations using ECD/ETD have generally been limited to synthetic glycopeptides or single glycoproteins (41)(42)(43)(44)(45) (46). We have previously developed a sialic acid specific capture-and-release protocol for the enrichment of both N-and O-glycosylated peptides from sialylated glycoproteins in biological samples using hydrazide chemistry (37).…”
mentioning
confidence: 99%
“…Several studies have demonstrated the value of mass spectrometry (MS) in identifying Gal-deficient IgA1 in patients with IgAN (16 -21), including our work that demonstrated the first direct localization of native sites of O-glycan chains in the hinge region (HR) of IgA1 by use of electron capture dissociation (ECD) (20,22). ECD and the more recently developed electron transfer dissociation (ETD) have been used to identify sites of O-glycosylation on a variety of proteins (23)(24)(25)(26). This includes the analysis of sites of O-glycosylation by on-line LC-ECD/ETD MS/MS methods (23,26,27).…”
mentioning
confidence: 99%
“…ECD and the more recently developed electron transfer dissociation (ETD) have been used to identify sites of O-glycosylation on a variety of proteins (23)(24)(25)(26). This includes the analysis of sites of O-glycosylation by on-line LC-ECD/ETD MS/MS methods (23,26,27).…”
mentioning
confidence: 99%